A Myth of Beauty Concept on Avoskin Skincare Advertisement - Destri Mutiara Rezky (LPPM STBA Persada Bunda, 2024)
Myths can shape society and influence people’s behaviour. They play a very important role in society, as a genre of folklore. In advertising, the meaning process occurs at two stages, namely denotative and connotative. Advertisers often use this mythical level to appeal to consumers' emotions and associate them with their products. Based on explanation above, this research purpose to identify the denotation, connotation, and myth of beauty concept contained in three skincare advertisements there are Avoskin, Oasea, and NPure, taken from each official Instagram brand. In this research, researcher used semiotic theory to explore the meaning of signs in each advertisement scene from Roland Barthes. The research method used descriptive qualitative research, it means research that focuses on describing and interpreting the data analysis process. The data collection technique is documentation, by means of screenshots in each scene that appears in the advertisement. The results and conclusions of this research is the researcher identify several meanings of denotation, connotation and beauty myths in each scene in the advertisement. The most common beauty myth found in these three advertisements is symbolized by attitudes, behaviour, human facial expressions, and natural conditions. It can be concluded that beauty is not only based on the physical but can be symbolized in different forms.